lncRNA SNHG5 promotes cell proliferation, migration and invasion in oral squamous cell carcinoma by sponging miR-655-3p/FZD4 axis - Yu, Lijiang (Oncol Lett, 2020)
Recently, previous studies have shown that long non-coding RNA (lncRNA) can act as a tumor promoter or inhibitor in the pathogenesis of oral squamous cell carcinoma (OSCC). However, the regulatory mechanism of lncRNA SNHG5 is unknown in OSCC. Therefore, the functional mechanism of lncRNA SNHG5 in OSCC was initially revealed in this study. Here, RT-qPCR and western blot analysis were used to assess mRNA and protein expression. The functional mechanism of SNHG5 was investigated by MTT, Transwell and luciferase reporter assays. The results showed that SNHG5 expression was upregulated in OSCC and promoted the viability, migration and invasion of OSCC cells. In addition, SNHG5 is the sponge of miR-655-3p in OSCC. And miR-655-3p was found to play an inhibitory effect in OSCC by interacting with SNHG5. Moreover, miR-655-3p directly targets FZD4 and negatively regulates its expression in OSCC. Functionally, FZD4 promoted the progression of OSCC by interacting with the SNHG5/miR-655-3p axis. In conclusion, lncRNA SNHG5 promotes cell proliferation, migration and invasion in OSCC by regulating miR-655-3p/FZD4 axis.